THE CONCEPT OF IT EDUCATION IN UKRAINE - Lutskiy, M. (Science-based technologies, 2013)
Large corporations and IT-companies are considered as the pioneers of conception of «double education»: obligatory base preparation and additional certificated education at the applied courses. This ideology allows students to gain an university diploma within the special educational IT-courses. Co-operation between an university and IT-companies directed on advancement of practical disciplines and specialized courses for the complete higher education getting is a necessary requirement for development of information security (IS). In article the conceptual solutions of questions of preparation, retraining and in-plant training of staff in information security field are discussed in the conditions of their accordance to international standards. Questions that must be defined by this conception: circle of problems and proper purpose of educational field «Information security» introduction, and also comparative analysis and ways of solution of this problem in obedience to international standards and requirements. Derivatives from the adopted conception are a level, functions and maintenance of teaching of specialist in information security field.